2012
DOI: 10.1007/s13197-012-0688-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of vacuum packaging and refrigerated storage on the chemical quality of paneer tikka

Abstract: Paneer tikka, a popular dish for vegetarians, is a tongue tingling favourite of Indian gourmets. It is a perishable commodity which requires more than five hours for its preparation. The shelf life of paneer tikka is hardly one day at room temperature which impedes its proper marketing. In order to enhance the shelf life of paneer tikka, the product was vacuum packed in two high barrier packages, viz., LLDPE * /BA † /Nylon-6/BA/LDPE ‡ (110 μ, * linear low density polyethylene, † binding agent, ‡ low density po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Slower rate of proteolysis was reported for white cheese (Turkish cheese) under vacuum compared to non-vacuum conditions stored at 4-5 o C for 90 days (Cinbas and Kilic, 2006). Ahuja and Goyal (2013) reported that increase in concentrations of tyrosine content of vacuum packed paneer tikka samples during refrigerated vacuum storage for a period of 30 days and observed duration of storage as well as type of package significantly affected tyrosine content. Fuentes et al 2015, reported that proteolysis did not showed significant changes during storage in pasta filata mexican cheese during refrigerated vacuum storage for 24 days.…”
Section: Resultsmentioning
confidence: 99%
“…Slower rate of proteolysis was reported for white cheese (Turkish cheese) under vacuum compared to non-vacuum conditions stored at 4-5 o C for 90 days (Cinbas and Kilic, 2006). Ahuja and Goyal (2013) reported that increase in concentrations of tyrosine content of vacuum packed paneer tikka samples during refrigerated vacuum storage for a period of 30 days and observed duration of storage as well as type of package significantly affected tyrosine content. Fuentes et al 2015, reported that proteolysis did not showed significant changes during storage in pasta filata mexican cheese during refrigerated vacuum storage for 24 days.…”
Section: Resultsmentioning
confidence: 99%
“…Metal migration from utensils can occur due to various factors, including the type of metal used in electroplating, the thickness of the metal layer, the pH of the food or beverage, and the duration and temperature of contact between the utensil and the food or beverage [ 2–3 ] . Therefore, it is essential to assess the impact of electroplating on the migration of metal ions from utensils into food and beverages [ 4–6 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, attempts have been made to increase the shelf‐life of paneer by using modified atmosphere, vacuum, and antimicrobial packaging techniques for quality maintenance, effective marketing, and consumer convenience (Kandeepan et al., 2011; Rai et al., 2008; Sharma et al., 2019; Thippeswamy et al., 2011). Among these different packaging methodologies, vacuum packaging is widely accepted for paneer at an industrial scale because of its advantages in retarding oxidative deterioration and checking microbial growth in packed products (Ahuja & Goyal, 2013). Further, the product storage stability also depends on the quality of raw materials and ingredients used in processing, manufacturing process, and microbial load of the developed product prior to packaging.…”
Section: Introductionmentioning
confidence: 99%